George Short Movie's Search for Semiotic Aspects - Kharris Nur Qotimah (Universitas Pendidikan Indonesia, 2021)
George's film tells of a tall man with a yellow hat named Ted who is assigned to get artifacts for museum needs, then Ted or better known as the yellow hat goes to Africa to get valuable artifacts that are useful for attracting many visitors to the museum where he works. On the way, he meets a brown monkey who is always curious about anything. The yellow hat named the monkey by the name of George and they became friends and lived in a hotel in the middle of the city. The purpose of this study was to determine the semiotic aspects contained in the cartoon film